Persepsi E-Commerce Shopee terhadap Tingkat Daya Beli pada Pelanggan yang Berprofesi sebagai Karyawan - Utama, Dani Chandra; Rahman, Arif; Ariandi, Fajri; Arista, Roynaldi (Jurnal Informatika Ekonomi Bisnis, 2022)
Buyers who work as employees are customers who are sales targets. This study aims to analyze the perceptions of customers who work as employees of E-Commerce Shopee. This analysis becomes a reference in identifying the level of purchasing power on the influence of price, promotion and quality of service. The data studied is the purchase intention of employees of PT Caterpillar Indonesia Batam. This study uses a quantitative descriptive method. The sampling technique was purposive sampling, namely 50 Shopee users as an employee online shopping platform. The results of this study show that based on the t test, price perceptions have a positive and insignificant effect on purchase intention, and based on the t test, promotion and service quality have a positive and significant effect on purchase intention. Based on the calculated t value for the price perception variable (X1) is 3.167, with a sig value of 0.146, the Promotion variable (X2) is 3.175 with a sig value of 0.325, the Service Quality variable (X3) is 0.225 with a sig value of 0.757. These results indicate that the perceived price, promotion, and service quality variables have a positive and partially significant effect on the purchase intention variable. The value of the regression equation test is 0.762, 0.780 and 0.678 which means that the relationship between perceptions of price, promotion, and service quality with employee performance is positive and significant. While the test results of the coefficient of determination, namely employee buying interest of 0.686 or 68.6%, are influenced by perceived price, promotion and service quality factors, while the rest are influenced by other factors.